Stavba v krajině - Winery - Nováková, Jitka (Vysoké učení technické v Brně. Fakulta architektury)
Stavba vinařství je umístěna v krajině nedaleko obce Strachotín na Jižní Moravě. Řešené území se prudce svažuje směrem na jih k hladině vodní nádrže Nové Mlýny. Na budovu výroby navazuje objekt prezentace, degustace a prodeje vín. Součástí areálu je centrum volného času s objekty pro ubytování a s možností návštěvy wellness, seminárních místností, restaurace a kavárny. Budovy ubytování a některé další jsou navrženy jako energeticky soběstačné dřevostavby využívající energii z obnovitelných přírodních zdrojů.

Building structure of wine-growing is situated in the countryside not far from the village Strachotin in South Moravia. Concerned area slopes wildly down to the level of the water reservoir. To the building of production concures parts of presentation, degustation, and distribution of wine. This area includes also leisure centre with possibility of accomodation , visit of wellness, seminary rooms, restaurant and coffee. Buildings for accomodation and some other are designed as energetically selfsufficient wooden structures using energy from renewable natural resources.
Architecture in landscape - Winery
Keywords: VINAŘSTVÍ - ROZKLAD A SESTUP; WINERY - DECOMPOSITION AND DESCENT